Macrophages: An Inflammatory Link Between Angiogenesis and Lymphangiogenesis. (5th February 2016) - Corliss, Bruce A.; Azimi, Mohammad S.; Munson, Jennifer M.; Peirce, Shayn M.; Murfee, Walter L.
Abstract: Angiogenesis and lymphangiogenesis often occur in response to tissue injury or in the presence of pathology (e.g., cancer), and it is these types of environments in which macrophages are activated and increased in number. Moreover, the blood vascular microcirculation and the lymphatic circulation serve as the conduits for entry and exit for monocyte‐derived macrophages in nearly every tissue and organ. Macrophages both affect and are affected by the vessels through which they travel. Therefore, it is not surprising that examination of macrophage behaviors in both angiogenesis and lymphangiogenesis has yielded interesting observations that suggest macrophages may be key regulators of these complex growth and remodeling processes. In this review, we will take a closer look at macrophages through the lens of angiogenesis and lymphangiogenesis, examining how their dynamic behaviors may regulate vessel sprouting and function. We present macrophages as a cellular link that spatially and temporally connects angiogenesis with lymphangiogenesis, in both physiological growth and in pathological adaptations, such as tumorigenesis. As such, attempts to therapeutically target macrophages in order to affect these processes may be particularly effective, and studying macrophages in both settings will accelerate the field's understanding of this important cell type in health and disease.